EFFECTIVENESS OF HOME-BASED CARE AND MULTI-FAMILY GROUP SUPPORT ON COPING AND TREATMENT ADHERENCE IN TUBERCULOSIS CLIENTS - Ester Radandima; Kartini Pekabanda; Antonetha Rosni Hunggumila; Irene Febriany Mamo Kitu; Veronika Toru (Bajang Institute, 2026)
Background : Tuberculosis (TB) is still a global health problem with low levels of medication adherence as one of the causes of drug resistance. Home-Based Care with Multi-Family Group Support programs are seen as able to improve coping strategies and client compliance. Objective: To determine the influence of the Home-Based Care Program with the Multi-Family Group Support approach on coping strategies and treatment adherence of TB clients. Methods: A quasi-experimental study with a pre-test post-test with control group design involved 56 TB respondents who were divided into intervention and control groups. The research instrument used a coping strategy questionnaire (COPE Inventory) and a treatment compliance observation sheet. Data analysis was carried out in univariate, bivariate (paired t-test, independent t-test), and multivariate (linear regression test). Results: There was a significant improvement in adaptive coping strategies (p<0.05) and medication adherence (p<0.05) in the intervention group compared to the controls. The most influential factors were family support and the intensity of group meetings. Conclusion: The Home-Based Care Program with a Multi-Family Group Support approach effectively improves coping strategies and treatment adherence in TB patients. The Home-Based Care Program with a Multi-Family Group Support approach is effective in improving coping strategies and treatment adherence in TB clients.